Belgium : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
Belgium has effected a remarkable fiscal adjustment, best illustrated by the decline in its public debt. While benefiting from an appreciable decline in interest rates, most of the underlying consolidation reflected a considerable increase in the tax burden, one of the highest in the Organisation for Economic Cooperation and Development. This paper analyzes the social transfer system in Belgium. Belgium has a very accessible and equitable health care system. The system is characterized by high input levels and service volumes.